Diffusion tensor imaging (DTI) and plasma p-tau 181 in Alzheimer’s disease - Fardin Nabizadeh; Seyed Behnamedin Jameie (Neurology Letters, 2022)
Alzheimer’s Disease (AD) is characterized by cognitive impairments and memory difficulties, which cause daily activities, and personal and behavioral problems. In recent years blood-based biomarkers like plasma phosphorylated tau protein at threonine 181 (p tau 181) emerged as new tools and showed a sufficient power in detecting AD patients from healthy people. Here we investigate the correlation between p tau 181 and white matter microstructural changes in AD patients. We add 21 Alzheimer diagnosed patients with baseline plasma p tau level, CSF Amyloidβ, CSF Tau, CSF p Tau, and DTI metrics from the ADNI database. The analysis revealed that the plasma level of p tau 181 could predict changes in MD, RD, AD, and FA parameters in several regions Also, there is a significant association between white matter pathways alteration in different regions with each of the CSF biomarkers. In conclusion, our study results show that plasma p tau 181 levels are associated with microstructural changes in pathogenesis areas of Alzheimer's disease, which enhance this biomarker's diagnostic status. Longitudinal studies are also necessary to prove the efficacy of these biomarkers and predicting role in structural changes.